Numerical Simulation of Velocity Field around Two Columns of Tandem Piers of the Longitudinal Bridge - Hongliang Qi; Junxing Zheng; Chenguang Zhang (Fluids, 2020)
This research explores the effects of different spans of two columns of tandem piers on the characteristics of x-velocity near the river bed based on computational fluid dynamics (CFD) simulations. With a span shorter than 27.5D (D is the diameter of piers), the shape and the lateral range of the x-velocity increases with the increase of distance downwards the x-direction. For the area between the tandem piers and the wall, the VRi/VR1 (the ratio of the x-velocity at the i-th row to the x-velocity of the first row in each model) near the wall increases up to 1.26. For the area between the two columns of tandem piers, the profile of VRi/VR1 changes from a “∩-shape” to an “M-shape” in each model. RAVC (average velocity change ratio) of different spans increases gradually and tends to be stable with the increases of the span. The largest RAVC is about −17.66% with a span of 0.52 m. The RMV (the ratio of the maximum x-velocity among piers in each row in different models to the maximum x-velocity of the two piers arranged side by side) of piers in the first row of different models is around 0.95. The RMV becomes 0.82 at the second pier in each model when the span is shorter than 27.5D, and increases to 0.91 if the span is longer than 27.5D. If the span is longer than 27.5D, the RMV of different piers are close to each other from the 2nd pier to the last one.